2019
DOI: 10.1007/s12402-018-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory (partially) mediates the link between ADHD symptoms and procrastination

Abstract: Individuals with attention deficit hyperactivity disorder (ADHD) often show poor planning and poor organization of tasks and activities which has been related to reduced memory for delayed intentions (prospective memory) and procrastination-in addition to other cognitive or motivational factors. This study set out to bring the fields of prospective memory and procrastination research together and to explore possible relations between the two constructs in ADHD. Twenty-nine adults with ADHD and 24 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
3
6
1
Order By: Relevance
“…As a consequence, retention-intervals may often be particularly long for procrastinators, whichas our data showscan lead to more PM failures. Our findings also cohere with Altgassen et al (2019) who suggested a negative link between PM and procrastination. However, Altgassen et al (2019) only used a self-reported questionnaire to assess procrastination and they focused on individuals with ADHD.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As a consequence, retention-intervals may often be particularly long for procrastinators, whichas our data showscan lead to more PM failures. Our findings also cohere with Altgassen et al (2019) who suggested a negative link between PM and procrastination. However, Altgassen et al (2019) only used a self-reported questionnaire to assess procrastination and they focused on individuals with ADHD.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings also cohere with Altgassen et al (2019) who suggested a negative link between PM and procrastination. However, Altgassen et al (2019) only used a self-reported questionnaire to assess procrastination and they focused on individuals with ADHD. The present study hereby goes one step further and corroborates these findings with an objective, behavioral measure and it extends the association of procrastination and PM for the first time to a more general, non-clinical population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These include an assessment of the impact of successful learning of self-regulation on reward processing in children with ADHD (Baumeister et al 2019). We also take up the question of the specificity of reaction time variability for ADHD (Salum et al 2019), and the mediation of the link between ADHD symptoms and procrastination by prospective memory (Altgassen et al 2019). Furthermore, this issue discusses whether the Test of Variables of Attention (TOVA) has a practical effect on adult ADHD (Manor 2019) and focuses on ADHD as a frequent, hidden comorbidity in adult psychiatric patients (Bitter et al 2019).…”
mentioning
confidence: 99%